Responsabilidade civil aplicada à atividade notarial e registral sob a ótica da análise econômica do direito - Medeiros, Victória Gandolfi (2024)
This dissertation addresses the complex issue of notarial and registry civil liability in the Brazilian context, exploring it in light of the Economic Analysis of Law, with the general objective of analyzing the impact of the economic analysis of law on the civil liability of notaries and registrars in Brazil, exploring the economic factors that influence the civil liability of these professionals and proposing recommendations to improve the legislation and regulation of notarial and registry services in the country. The study aims to answer the research problem: "How can the doctrine of the Economic Analysis of Law and its tools contribute to the determination of civil liability for errors committed by notary offices?". The dissertation begins by analyzing the legal and constitutional bases of notarial activities. Then, it delves into the civil liability of notaries and registrars, and the liability of the State for the acts of notaries and official registrars who, in the exercise of their functions, cause harm to third parties, as established by Brazilian doctrine and jurisprudence. The second part of the dissertation introduces the Economic Analysis of Law, promoting interdisciplinarity between economics and law. Grounded in economic theory, the Economic Analysis of Law is crucial to understanding the economic foundations underlying notarial offices, including rationality, efficiency, and externalities. The practical application of the Economic Analysis of Law to notarial and registry activities is explored, highlighting its potential in the analysis of these services. In the third and final chapter, the Economic Analysis of Law is applied to the study of notarial and registry civil liability, with a special focus on Extraordinary Appeal No. 842,846 of the State of Santa Catarina. The analysis of incentives, the efficiency of control and supervision mechanisms, and the role of the State in preventing and repairing damages resulting from notarial errors are discussed in depth. The results obtained highlight the relevance of the Economic Analysis of Law as an analytical tool in understanding the economic dynamics involved in civil and state liabilities. It is concluded that the application of these foundations contributes not only to a more comprehensive understanding of the challenges faced by notarial offices, but also to the improvement of public policies and pertinent regulations.